Translation to Spanish and linguistic validation of the Canine Brief Pain Inventory - Olcoz, María; Cabezas, Miguel Ángel; Rocca, Giorgia della; Gómez de Segura, Ignacio A. (Frontiers in Veterinary Science, 2023)
Pain scales for the assessment of chronic pain have been developed for dogs but they should be translated and linguistically validated to be used by owners with different native languages. The Canine Brief Pain Inventory (CBPI) is widely employed for this purpose but has not been translated into Spanish. Thus, the aim was to produce a validated translation of the Spanish CBPI. The original English version of the CBPI was analysed and translated by two native linguists of the target language and both revised by a third native linguist to identify potential discrepancies and create a unified translation (reconciliation). Then, an independent linguist with native fluency in English and the target language drafted the back-translation. Finally, the research team confronted both the original and the back-translation to identify and solve relevant differences. Once the translated version was produced, a cognitive debriefing was performed to assess the questionnaire in the target population. A total of 50 surveys were conducted to dog owners of different ages, sex, and socio-economic characteristics. All respondents considered the survey to be clear and a final version of the Spanish CBPI has been produced.